Panama : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
This paper presents empirical evidence on the effects of achieving investment grade on borrowing costs for the sovereign and the private sector. This study provides background information on sovereign credit ratings and compares Panama's key macroeconomic and institutional characteristics with those of other emerging markets. Statistical evidence on the reduction in sovereign spreads associated with obtaining investment grade status and the impact of the sovereign's upgrade on corporate financing costs were also discussed. The model is estimated using a variety of panel regression techniques.